Neutralization of a bothropic PLA2-like protein by caftaric acid, a novel potent inhibitor of ophidian myotoxicity - Cardoso, Fábio F. [UNESP] (2020)
Envenoming by snakebite is an important global health issue that has received little attention, leading the World Health Organization to naming it as neglected tropical disease. Several snakebites present serious local symptoms manifested on victims that may not be efficiently neutralized by serum therapy. Phospholipase A2-like (PLA2-like) toxins are present in Viperidae venoms and are responsible for local myotoxic activity. Herein, we investigated the association between BthTX-I toxin and caftaric acid (CFT), a molecule present in plants. CFT neutralized neuromuscular blocking and muscle-damaging activities promoted by BthTX-I. Calorimetric and light-scattering assays demonstrated that CFT inhibitor interacted with dimeric BthTX-I. Bioinformatics simulations indicated that CFT inhibitor binds to the toxin's hydrophobic channel (HCh). According to the current myotoxic mechanism, three different regions of PLA2-like toxins have specific tasks: protein allosteric activation (HCh), membrane dockage (MDoS), and membrane rupture (MDiS). We propose CFT inhibitor interferes with the allosteric activation, which is related to the conformation change leading to the exposure/alignment of MDoS/MDiS region. This is the first report of a PLA2-like toxin fully inhibited by a compound that interacts only with its HCh region. Thus, CFT is a novel candidate to complement serum therapy and improve the treatment of snakebite.